2016
DOI: 10.1080/09500340.2016.1220643
|View full text |Cite
|
Sign up to set email alerts
|

Afterpulsing model based on the quasi-continuous distribution of deep levels in single-photon avalanche diodes

Abstract: We have performed a statistical characterization of the effect of afterpulsing in a free-running silicon single-photon detector by measuring the distribution of afterpulse waiting times in response to pulsed illumination and fitting it by a sum of exponentials. We show that a high degree of goodness of fit can be obtained for 5 exponentials, but the physical meaning of estimated characteristic times is dubious. We show that a continuous limit of the sum of exponentials with a uniform density between the limiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Ref. 19 showed that the hyperbolic sinc model was better than the power law model using id100-MMF50 SPAD module from idQuantique, we were able to duplicate those results only with 6 of the 16 detectors we tested.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Ref. 19 showed that the hyperbolic sinc model was better than the power law model using id100-MMF50 SPAD module from idQuantique, we were able to duplicate those results only with 6 of the 16 detectors we tested.…”
Section: Resultsmentioning
confidence: 91%
“…We define the total afterpulse probability to be the sum total of the afterpulse probability in each bin of the corrected g (2) histogram for a duration of 900 ns (We chose a value of 900 ns such that we include a significant amount of the afterpulse tail while avoiding any potential effects due to the earliest possible subsequent pulse 1 μ s later. In silicon based SPADs the afterpulse tail dies off some hundred nanoseconds, whereas in InGaAs detectors it can last for several μ s) 18 , 19 . Regardless of the model, in order to obtain a good fit we had to ignore the first two points of the afterpulse tail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the photonic scenario just described, bias may arise from sources such as imperfect state preparation with nonequalized amplitudes, a polarizing beam splitter that does not reliably separate H and V polarizations, and imbalanced detectors. Correlations may be caused, for example, by dead-time and afterpulsing effects in the detectors [29,31,32]. In practical implementations, these imperfections often have a significant influence and can be difficult to avoid [6].…”
Section: Introductionmentioning
confidence: 99%
“…The two main effects in the behavior of our APDs which can introduce undesired correlations in the resulting sequences of bits are called after-pulsing and dead time [22,23]. The first effect, roughly speaking, corresponds to a false detection event due to the residual effects of an avalanche triggered by a previous event, while the dead time is the time period after each event during which the system is not able to record a subsequent incoming optical signal.…”
Section: Apd Effects On Introducing Correlationsmentioning
confidence: 99%